The Effect of Active Substance X on Skin Affected by Cellulite - Vorobjova, Diana; Gierasimovič, Zita (Slauga. Mokslas ir praktika, 2023)
Increased fat cell accumulation due to overweight creates an aesthetic problem, resulting in cellulite. Active substance X penetrates into the deeper layers of the skin affected by cellulite, activates microcirculation, optimizes the effect of active substances, and reduces cellulite in affected areas of the body.The aim. Assessing the effect of active substance X on cellulite-damaged thigh skin.The research method. Two study participants were selected by targeted screening, meeting the study criteria: female gender, aged 20-25, having stage II-III cellulite, without any contraindications that would prevent procedures with X active substance. A course of 6 procedures is planned. According to the procedure protocol, the frequency of the procedures is performed every 2-3 days depending on the stage of cellulite. During the research stages, the following tools are used: a client card,a measuring tape, a calliper, and photogrammetry. The obtained data is archived and analysed.The results and conclusions. Positive changes in the signs of the two-component X active substance were observed in both study participants after a course of six procedures. The cellulite of the T1 study participant progressed from stage III liposclerosis with hardening to stage II fibrous cellulite. The T2 study participant progressed from stage II fibrous cellulite to stage I oedematous cellulite.
Keywords: skin; cellulite; stages of damage; active substance